Bahasa Inggris - Rizqullah, Ayun Anindita (International Journal Administration, Business & Organization, 2023)
The purpose of this study is to investigate the effect of Instagram feeds on the buying interest of students in the city of Bandung. This study uses a quantitative description method. Data collection was carried out by distributing questionnaires to students in the city of Bandung with a total of 110 respondents. The analytical method used is simple linear regression analysis with the aim of knowing the effect of the x variable (Instagram Feed) on the y variable (bandung city students). The results of this analysis are that the appearance of the Instagram feed has an influence of 66.6% on the buying interest of students in the city of Bandung